Effect Of Wearable Tubing Assistive Walking Device on Anterior Tibial Muscle Activity at Swing Phase in Post-Stroke Patients - Tri Rahayu Septyaningrum; Subagyo Subagyo; R.A. Meisy Andriana; I Putu Alit Pawana (Surabaya Physical Medicine and Rehabilitation Journal, 2023)
Background: One-third of post-stroke patients experience gait disturbance which is commonly associated with drop foot at three months after acute stroke. One of the orthoses that are proposed to improve gait in stroke patient is Wearable Tubing Assistive Walking Devices (WTAWD). It is hypothesized that WTAWD reduce the anterior tibial muscle activity which may become hyperactive during the swing phase in post-stroke patient with drop foot as an attempt to perform foot clearance. Aim: This study aims to investigate the effect of WTAWD on anterior tibial muscle activity during the swing phase in post-stroke patients. Material and Methods: Eleven patients, aged 30-60 years, with post-stroke hemiparesis in the subacute and chronic phase who fulfill the inclusion criteria are chosen as research subjects. The subjects were asked to wear WTAWD on the leg with weakness. Surface Electromyography (sEMG) examination of anterior tibial muscle was performed when the patient walked with and without wearing the WTAWD. Results: All 11 subjects completed the sessions and study protocol, with no losses throughout the study. None of the subjects reported any adverse effects during or after the intervention. A significant reduction of sEMG value on anterior tibial muscle activity was found when the patient wore WTAWD (p=0.001). Conclusion: There is an effect of WTAWD on decreasing anterior tibial muscle activity during the swing phase in post-stroke patients. Further research is needed to measure the kinematic and temporospatial values to increase knowledge about the effect of additional WTAWD to improve gait in stroke patients.